Supporting a Medical Diagnostic Process by Selected AI Methods: an Asperger Syndrome Case Study - Kakiashvili, Tamar; Koczkodaj, Waldemar; Matheson, Duncan; Montgomery, Phyllis; Passi, Kalpdrun; Rybakowski, Filip; Tadeusiewicz, Ryszard; Woodbury-Smith, Marc (Studia Informatica. System and information technology, 2008)
A medical knowledge-driven diagnostic process can be supported by AI methods as presented here by an Asperger Syndrome case study. Two methods: consistency-driven pairwise comparisons (CDPC) and automatic understanding (AU) are presented in this study. Deficiencies of a data-driven model for the medical diagnostic process and clinical reasoning are also discussed.